Respuesta :

Answer:

A. √(e + 14)

Step-by-step explanation:

[tex]\frac{dy}{dx} = \frac{e^{x} - 1}{2y}[/tex]

separating the variables, we have

2ydy = ([tex]e^{x}[/tex] - 1)dx

integrating, we have

∫ydy = ∫([tex]e^{x}[/tex] - 1)dx

∫ydy = ∫[tex]e^{x}[/tex]dx - ∫1dx + C

2y²/2 = [tex]e^{x}[/tex] - x + C

y² = [tex]e^{x}[/tex] - x + C

when x = 0, y = 4

So,

y² = [tex]e^{x}[/tex] - x + C

4² = [tex]e^{0}[/tex] - 0 + C

16 = 1 + C

16 = 1 + C

C = 16 - 1

C = 15

So,

y² = [tex]e^{x}[/tex] - x + 15

when x = 1, we find y

y² = [tex]e^{1}[/tex] - 1 + 15

y² = e + 14

y = √(e + 14)